Edukasi dan Pendampingan Pembuatan Nomor Induk Berusaha (NIB) untuk Legalitas UMKM di Kelurahan Kilasah Kecamatan Kasemen - Ahmad Gani; Maulana Deni Erlangga; Deti Cahyati; Ulinnuha Ulinnuha; Syamsul Hidayat (Lembaga Pengembangan Kinerja Dosen, 2024)
The existence of micro businesses for a country is important and is an indicator for assessing societal civilization. In reality, the current conditions in society are that there are still many micro business actors who do not know and have not registered a business permit, one of which is the residents of Kilasah Village, Kasemen District, Serang City. This can happen because of the lack of literacy regarding business legality and the benefits of NIB. So under these conditions, tum PkM provides assistance in making NIBs to MSMEs in Kilasah Village as a solution to the problem of not developing their businesses. The implementation of PkM goes through four stages, namely the observation stage of partner problems, the preparation stage, the implementation stage which contains providing education and motivation for registering business legality, as well as filling out the NIB form directly to the MUI. The result of this activity is that through the mentoring program for making NIB business legality, MSME actors in Kilasah Village understand NIB and understand the benefits of legality of their business. Through the mentoring program for making NIB business legality, MSME actors in Kilasah Village understand and can practice the steps and flow, as well as procedures for making NIB. The results obtained prove the success of the PkM team in helping assist MSMEs residents of Kilasah Village in creating Business Identification Numbers (NIB) that can develop their businesses with standardized products.